Effect of Phosphorus Sources on Nodulation and Dry Matter Yield of Pigeonpea - Yanquoi, H. (University of Ghana, 2014)
Phosphorus (P) is an essential element which has been identified as a major plant nutrient that limits nitrogen (N2) fixation in legumes. Different sources of water soluble P have been used to increase growth, nodulation and N2 fixation in legumes , but there is inadequate information on the effect of phosphate rocks (PRs) on the growth, nodulation, and N2 fixation of pigeonpea. In this study, Togo rock phosphate (TRP), and water soluble triple superphosphate (TSP) were used to test the effect of P application on dry matter yield and nodulation of pigeonpea. The objectives of the study were to (i) compare Togo rock phosphate with Triple super phosphate with respect to: dry matter yield and nodulation of pigeonpea using two soil series (Toje and Bumbi), (ii) assess the rate of phosphorus application for maximum dry matter yield and nodulation in pigeonpea and (iii) compare the agronomic effectiveness of the two P sources in a green house experiment. The study was carried out in pots with phosphorus application rates of 0, 30, 60, 90, 120, and 150 kg P/ha and pigeonpea was used as a test crop. The plants were grown and harvested 6 weeks after planting. The shoots were analyzed for dry matter yield and phosphorus uptake and root nodule numbers were counted and weighed. The relative agronomic effectiveness (RAE) of the Togo rock phosphate was calculated using the dry matter yield and P uptake at 120 kg P/ha application rate. The results of the pot experiment showed that the dry matter yield (DMY) of the pigeonpea crop increased consistently from 0-P kg/ha to 120 kg P/ha and decreased at 150 kg P/ha in both soils. The DMY, nodule numbers and weight in the Toje soil series were significantly higher than in the Bumbi soil despite the relatively higher fertility status of the Bumbi soil series (p < 0.05). This suggests that soil fertility is not the only parameter to be considered for growth and development of crops. For soil productivity, both the chemical and the physical properties are equally important since they both contribute to the root development and exploration for nutrients and water in the soil. Dry matter yield, nodule numbers and weight of the pigeonpea obtained in the TSP treatments were significantly higher than those of the Togo rock phosphate treatments. The agronomic effectiveness of the TRP in the two soils showed that in the Toje soil series, the RAE was 27 % and in the Bumbi soil series, it was 18 % that of the TSP. This could be attributed to the fact that the Togo rock phosphate did not dissolve adequately well to supply the needed P to the pigeonpea during the six weeks growing period.
Thesis (M.Agric.) - University of Ghana, 2014